Sintering method for effectively reducing ferromagnetic resonance line width of Bi-substituted garnet ferrite with high dielectric constant

Through the sintering method of heating-multi-stage high-temperature and low-temperature alternating-cooling, the problem of Bi replacing the ferromagnetic resonance line width of garnet ferrite is solved, reducing magnetic loss, improving grain size and sintering quality, and promoting Miniaturization and mass production of microwave ferrite devices.

CN119263799APending Publication Date: 2025-01-07SOUTHWEST INST OF APPLIED MAGNETICS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411298034.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the ferromagnetic resonance line width of Bi-substituted high-dielectric constant garnet ferrite, resulting in an increase in magnetic loss, affecting the miniaturization of microwave devices and the application of high-dielectric ferrite.

Method used

The sintering method of heating-multi-stage high-temperature and low-temperature alternating-cooling is adopted. By experiencing at least two high-temperature insulation sections and low-temperature insulation sections, the sintering temperature and time are controlled to avoid oversintering and abnormal growth of grains.

Benefits of technology

It significantly reduces the ferromagnetic resonance line width, improves grain size and sintering quality, and is suitable for Bi3+-substituted garnet-type high-dielectric constant microwave ferrite, improves the reliability and stability of mass production, and promotes microwave iron The development of miniaturization of oxygen device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263799A_ABST
    Figure CN119263799A_ABST
Patent Text Reader

Abstract

The invention discloses a sintering method for effectively reducing the ferromagnetic resonance line width of Bi-substituted garnet ferrite with a high dielectric constant, and belongs to the technical field of ferrite materials, the sintering method is a sintering route of heating-multi-stage high and low temperature alternation-cooling. According to the preparation method, the ferromagnetic resonance line width delta H of the garnet type high-dielectric-constant ferrite is improved, the grain size is increased, abnormal growth of grains after long-time sintering is avoided, the sintering difficulty of the Bi-substituted high-dielectric-constant microwave ferrite is reduced, the sintering quality of the ferrite is improved, and the sintering cost is reduced. The improvement of the batch production reliability and stability of the garnet high-dielectric-constant ferrite is facilitated, the development of a batch production process of high-dielectric-constant products is promoted, and the miniaturization development of microwave ferrite devices in China is assisted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ferrite materials, and in particular to a sintering method for effectively reducing the ferromagnetic resonance line width of Bi-substituted high dielectric constant garnet ferrite. Background Art

[0002] In order to reduce the size of microwave devices such as circulators and isolators and reduce the difficulty of miniaturization design of microwave devices, the high dielectric constant of microwave ferrite has become an important research direction of microwave ferrite materials. 3+ Replace Y 3+ To improve the dielectric constant of the material, but in actual research and development and production, it is found that the sintering temperature of conventional ferrite is generally above 1400℃, and the sintering temperature of high dielectric constant ferrite is greatly reduced due to the addition of low melting point oxide Bi2O3 (~830℃), which affects the grain growth and causes Bi 3+ Problems such as uneven distribution, small and uneven grain size, and decreased density increase the magnetic inhomogeneity of the material, increase the contribution of incomplete broadening of the solid phase reaction and anisotropic broadening to the ferromagnetic resonance line width ΔH, and increase the ferromagnetic resonance line width ΔH of high dielectric constant ferrites, thereby increasing the magnetic loss of microwave devices, affecting the application of high dielectric ferrites and the miniaturization of devices. In addition, larger and thicker green billets are often used for sintering in the production of ferrite substrates, which further reduces the sintering quality of high dielectric constant ferrites.

[0003] In order to solve the above problems, long-term insulation is generally used to improve the sintering quality of ferrite, extend the grain growth time as much as possible, reduce pores, increase density, and improve the ferromagnetic resonance line width. However, its effect is still difficult to cope with large-scale high-dielectric ferrite production, and insulation at one temperature for a long time can easily cause abnormal growth of ferrite, resulting in a sandy internal morphology and scrapping of ferrite.

[0004] Shenzhen Sunlord Electronics Co., Ltd. Nie Min et al. reported in "The Effect of Sintering Temperature on the Properties of High Bi Garnet Ferrite Materials" that the high dielectric ferrite prepared by sintering at 1030-1090℃ for 5h has a grain size of 1-2μm, a dielectric constant of 23.4, and a minimum ferromagnetic resonance line width ΔH of 46 Oe. Compared with the grains of conventional ferrites with a size of more than 10μm, the growth condition of this grain size is poor, and the line width is slightly higher; Zhou Yongchuan et al. from the Southwest Institute of Applied Magnetism 3+ The article "Effect of Substitution on the Properties of Polycrystalline Garnet Ferrite Materials" reported that high Bi 3+The designed high dielectric constant ferrite was substituted, and the minimum ferromagnetic resonance line width ΔH of the ferrite sintered at 880-1000℃ for 6h reached 50 Oe, and the grain size was about 1μm. Similarly, the results of this study showed that the ferrite grain growth under its formula and process was poor, and the line width parameter was slightly larger; Zhang Huaiwu et al. from the University of Electronic Science and Technology of China reported the effect of multi-step sintering method on the performance of low-temperature sintered ferrite in the article "Multi-step sintering processing of ferrites having enhanced magnetic properties". The multi-step sintering method used was a fixed total sintering time, and the sintering time of each stage decreased as the number of stages increased. For Y 2.1 Bi 0.9 Fe5O 12 The microwave ferrite is sintered at 950°C for a total holding time of 4 h. Due to its too short holding time, the ferrite grain size is only 1.48-1.55 μm, and the minimum ferromagnetic resonance line width ΔH is as high as 230 Oe. The ferrite obtained by this formula and preparation process has performance parameters that are more difficult to apply.

[0005] Therefore, it is very necessary to develop a sintering technology that can effectively improve the sintering quality and reduce the ferromagnetic resonance linewidth for the large-scale commercial application of high dielectric constant series microwave ferrites. Summary of the invention

[0006] The object of the present invention is to provide a sintering method for effectively reducing the ferromagnetic resonance line width of Bi-substituted high dielectric constant garnet ferrite, so as to solve the above problems.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A sintering method for effectively reducing the ferromagnetic resonance line width of Bi-substituted high dielectric constant garnet ferrite, the sintering method comprising heating-multi-stage high temperature and low temperature alternation-cooling.

[0008] As a preferred technical solution, the composition of the high dielectric constant garnet ferrite substituted by Bi is: Y 3-x-a Bi x Ca a M b Fe 5-b-δ O 12 , the M is selected from one of Sn, In, Zr, Ti, V, Al, and Ge, 0.8≤x≤1.6, 0.1≤b≤0.7, δ is the iron deficiency, 0.01≤δ≤0.1, and a is valence balanced according to the replacing element.

[0009] As a preferred technical solution, during sintering, a program-controlled bell furnace is used as the sintering furnace, and air or oxygen-containing atmosphere is used.

[0010] As a preferred technical solution, it takes 50 to 100 minutes to heat up to 100 ° C, 120 to 200 minutes to heat up to 200 ° C, 150 to 400 minutes to heat up to 400 ° C, and then heat up to 100 ° C to 200 ° C below the sintering temperature at a heating rate of ≤ 2.5 ° C / min, and finally heat up to the highest sintering temperature or a temperature within 15 ° C below the temperature in 150 minutes to 300 minutes. As a preferred technical solution, the multi-stage high-temperature and low-temperature alternating route is to go through at least two high-temperature insulation stages, such as: high-temperature insulation stage-cooling stage-low-temperature insulation stage-heating stage-high-temperature insulation stage.

[0011] As a further preferred technical solution, the insulation time of each high-temperature insulation section is not less than 5 hours, and the insulation temperature is within 15°C lower than the maximum temperature (the "maximum temperature" refers to the highest sintering temperature during the material sintering process, which is also the sintering temperature of the material formula itself, and the high-temperature insulation temperature is 0 to 15°C lower than the maximum temperature), the insulation time of each low-temperature insulation section is not less than 2 hours, the cooling section is 200 to 300°C below the sintering temperature, the cooling rate to the cooling section is 1°C / min to 2.5°C / min, and the heating rate from the low-temperature insulation section to the high-temperature insulation section is ≤2.5°C / min.

[0012] As a preferred technical solution, the cooling route is natural cooling or cooling at a rate of 1°C / min to 2.5°C / min. Depending on the size of the product, the cooling rate decreases as the size increases.

[0013] Through the sintering process of the present invention, the grain size is increased while over-burning is prevented, so as to achieve the purpose of improving the sintering quality of ferrite and reducing the ferromagnetic resonance line width.

[0014] The sintering method of the present invention is mainly aimed at Bi 3+ Substituted garnet type microwave ferrite; suitable for sintering of ferrite green body prepared by conventional solid phase process, suitable for both air and oxygen atmosphere; suitable for Bi 3+ The substituted high dielectric ferrite has two sintering temperature ranges, high temperature sintering and low temperature sintering. The ferrite ferromagnetic resonance line width ΔH prepared at low temperature (≤920°C) by the sintering method of the present invention can be reduced by more than 50 Oe, and the ferrite ferromagnetic resonance line width ΔH prepared at high temperature (950°C-1100°C) can be reduced by more than 20 Oe.

[0015] The present invention relies on a sintering bell furnace used for the production of conventional microwave ferrites. Aiming at the problem that Bi-substituted garnet-type high dielectric constant microwave ferrites are prone to deterioration of the ferromagnetic resonance line width ΔH, small sintered grains or abnormal growth, a sintering method suitable for this type of ferrite is designed. The sintering method can effectively reduce the ΔH of the ferrite and slightly increase the grain size while preventing abnormal grain growth. The effect is significant in both cases where the ferrite with a low Bi substitution amount has a higher sintering temperature and the ferrite with a high Bi substitution amount has a low sintering temperature.

[0016] Compared with the prior art, the advantages of the present invention are: the present invention improves the ferromagnetic resonance line width ΔH of garnet-type high dielectric constant ferrite and increases the grain size through the improvement of the sintering process, and avoids the abnormal grain growth under long-term sintering, reduces the sintering difficulty of Bi-substituted high dielectric constant microwave ferrite, improves the sintering quality of ferrite, helps to improve the mass production reliability and stability of garnet high dielectric constant ferrite, promotes the development of mass production technology of high dielectric constant products, and helps the miniaturization of microwave ferrite devices in my country. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The sintering flow chart is used for Example 1 of the present invention; Figure 2 The XRD spectrum of the ferrite obtained in Example 1 of the present invention; Figure 3 The XRD spectrum of the ferrite obtained in Example 3 of the present invention; Figure 4 This is a SEM image of the cross-section of the ferrite grains obtained in Example 1 of the present invention; Figure 5 This is a SEM image of the cross-section grains of the ferrite obtained in Comparative Example 1 of the present invention; Figure 6 This is a SEM image of the cross-section grains of ferrite obtained in Example 3 of the present invention; Figure 7 This is a SEM image of the cross-section grains of ferrite obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0018] The present invention will be further described below in conjunction with the accompanying drawings.

[0019] Example 1

[0020] A sintering method for effectively reducing the ferromagnetic resonance line width of Bi-substituted high dielectric constant garnet ferrite, This embodiment is for the chemical formula Y 3-x Bi x Ca y Sn y Fe 5-yO 12 , x=0.75, y=0.2 high dielectric constant garnet ferrite (low Bi substitution), weigh each raw material according to the chemical formula, the raw materials are Y2O3, Bi2O3, CaCO3, SnO2, Fe2O3. The weighed raw materials are subjected to the general preparation process of microwave ferrite, and are formed into ferrite green body through primary ball milling, pre-sintering, secondary ball milling, and granulation.

[0021] The ferrite green body is sintered in a bell furnace with air atmosphere. The specific sintering process is as follows: (1) The heating route is: 100 min to 100 °C, then 120 min to 200 °C, then 150 min to 400 °C, then 2.5 °C / min to 900 °C, and finally 300 min to 1050 °C; (2) The multi-stage high temperature-low temperature alternating route is: 1) The temperature rises to 1050℃ and then is kept for 5 hours, which is the insulation stage; 2) Cool down to 850℃ at 2.5℃ / min, which is the cooling stage; 3) 850℃ insulation for 2h, which is the low temperature insulation stage. 4) Then heat up to 1050℃ at a rate of 2.5℃ / min and keep warm for 5h; According to the above high temperature and low temperature alternation process, the material was kept at 1050℃ for 10 hours to complete the sintering stage. (3) Cool down to 850℃ at a rate of 2.5℃ / min and keep the temperature for 2h, then cool naturally to obtain high dielectric constant garnet ferrite. The sintering route is as shown in the attached figure. Figure 1 shown.

[0022] According to the microwave frequency application gyromagnetic material performance measurement method GB / T9633-2012, the ferromagnetic resonance line width ΔH, Curie temperature Tc, saturation magnetization 4πMs, relative dielectric constant ε of ferrite are measured. r The test results are shown in Table 1. The prepared materials were analyzed by X-ray diffraction analyzer (Panalytical X'Pert Powder, Netherlands). Figure 2 The ferrite grain microstructure was analyzed using a scanning electron microscope (ZEISS SIGMA 300, Germany). Figure 4 shown.

[0023] Example 2

[0024] A sintering method for effectively reducing the ferromagnetic resonance line width of Bi-substituted high dielectric constant garnet ferrite, This embodiment is for the chemical formula Y 3-x Bi x Ca y Sn y Fe 5-y O 12 , x=1.2, y=0.4, high dielectric constant garnet ferrite (high Bi substitution), weighing each raw material according to the chemical formula, the raw materials are Y2O3, Bi2O3, CaCO3, SnO2, Fe2O3; the weighed raw materials are subjected to a general preparation process of microwave ferrite, and are formed into a ferrite green body through a first ball milling, pre-sintering, a second ball milling, and granulation; The ferrite green body is sintered in a bell furnace with air atmosphere. The specific sintering process is as follows: (1) The heating route is: 100 min to 100 °C, then 120 min to 200 °C, then 150 min to 400 °C, then 800 °C at a heating rate of 2.5 °C / min, and finally 300 min to 1000 °C; (2) The multi-stage high temperature-low temperature alternating route is: 1) The temperature rises to 1000℃ and then is kept for 5 hours, which is the high temperature insulation stage; 2) Cool down to 800℃ at 2℃ / min, which is the cooling stage; 3) 800℃ insulation for 2h, which is the low temperature insulation stage. 4) Then increase the temperature to 1000℃ at a rate of 2.5℃ / min and keep it for 5h; According to the above-mentioned high temperature and low temperature alternating process, the material is kept at 1000℃ for 10h to complete the sintering stage; (3) The temperature is then cooled to 800°C at a rate of 2.5°C / min and kept at that temperature for 2 h. Finally, the temperature is cooled to 100°C at a rate of 1°C / min to obtain a high dielectric constant garnet ferrite.

[0025] According to the microwave frequency application gyromagnetic material performance measurement method GB / T9633-2012, the ferromagnetic resonance line width ΔH, Curie temperature Tc, saturation magnetization 4πMs, relative dielectric constant ε of ferrite are measured. r , loss tangent tanδ and other performance tests. The test results are shown in Table 1.

[0026] Example 3

[0027] A sintering method for effectively reducing the ferromagnetic resonance line width of Bi-substituted high dielectric constant garnet ferrite, This embodiment is for the chemical formula Y 3-x Bi x Ca y Zr y Fe5-y O 12 , x=1.6, y=0.55 high dielectric constant garnet ferrite (high Bi substitution), weigh each raw material according to the chemical formula, the raw materials are Y2O3, Bi2O3, CaCO3, ZrO2, Fe2O3. The weighed raw materials are subjected to the general preparation process of microwave ferrite, and are formed into ferrite green body through primary ball milling, pre-sintering, secondary ball milling, and granulation; The ferrite green body is sintered in a bell furnace using an oxygen atmosphere. The specific sintering process is as follows: (1) The heating route is: 100 min to 100 °C, then 120 min to 200 °C, then 150 min to 400 °C, then 2.5 °C / min to 720 °C, and finally 5 h to 915 °C (5 °C lower than the final sintering temperature of the material formula (920 °C)). (2) The multi-stage high temperature-low temperature alternating route is: 1) The temperature rises to 915℃ and then is kept for 5 hours, which is the high temperature holding stage; 2) Cool down to 720℃ at 1℃ / min, which is the cooling stage; 3) Keep at 720℃ for 2 h, which is the low temperature insulation stage; 4) Then increase the temperature to 915°C at a rate of 2.5°C / min and keep at this temperature for 5 h; The above-mentioned high temperature and low temperature alternating process is repeated, and the material is kept at 915℃ (the high temperature insulation temperature of 915℃ is 5℃ lower than the sintering temperature of 920℃ of the material itself, and the setting temperature of the high temperature insulation section can be adjusted within 15℃ on the basis of being lower than the sintering temperature of 920℃ of the material itself) for 15 hours (that is, the material formula is kept at 915℃ for 5 hours each time, and it goes through three times for a total of 15 hours) to complete the ferrite sintering section. (3) Finally, the temperature is lowered to 100°C at a cooling rate of 1°C / min to obtain a high dielectric constant garnet ferrite; According to the microwave frequency application gyromagnetic material performance measurement method GB / T9633-2012, the ferromagnetic resonance line width ΔH, Curie temperature Tc, saturation magnetization 4πMs, relative dielectric constant ε of ferrite are measured. r The test results are shown in Table 1. The prepared materials were analyzed by X-ray diffraction analyzer (Panalytical X'Pert Powder, Netherlands). Figure 3 The ferrite grain microstructure was analyzed using a scanning electron microscope (ZEISS SIGMA 300, Germany). Figure 6 shown.

[0028] Comparative Example 1 This comparative example is based on the aforementioned Example 1. The ferrite formula and green body preparation are consistent with those of Example 1. The green body is placed in a bell furnace and sintered using a conventional long-term heat preservation method. The air atmosphere is used. The specific sintering process is as follows: (1) The heating route is: 100 min to 100 °C, then 120 min to 200 °C, then 150 min to 400 °C, then 900 °C at a heating rate of 2.5 °C / min, and finally 5 h to 1050 °C; (2) The insulation route is: 1050℃ continuous insulation for 10 hours.

[0029] (3) The cooling route is consistent with step (3) of Example 1.

[0030] That is, the formula of the ferrite with low Bi substitution and the green body preparation described in Comparative Example 1 are the same as those in Example 1, and the continuous holding at 1050°C for 10 h in Comparative Example 1 is compared with the sintering route of the present invention in Example 1 at 1050°C for a total holding time of 10 h.

[0031] According to the microwave frequency application gyromagnetic material performance measurement method GB / T9633-2012, the ferromagnetic resonance line width ΔH, Curie temperature Tc, saturation magnetization 4πMs, relative dielectric constant ε of ferrite are measured. r The performance tests of ferrite and loss tangent tanδ are shown in Table 1. The ferrite grain microstructure was analyzed using a scanning electron microscope (ZEISS SIGMA 300, Germany). Figure 5 shown.

[0032] Comparative Example 2 This comparative example is based on Example 3, that is, the ferrite formula and green body preparation are consistent with Example 3, and the green body is placed in a bell furnace for sintering in an oxygen atmosphere. The specific sintering process is as follows: (1) The heating route is: 100 min to 100 °C, then 120 min to 200 °C, then 150 min to 400 °C, then 2.5 °C / min to 720 °C, and finally 5 h to 920 °C. (2) The insulation route is: 920℃ continuous insulation for 15 h.

[0033] (3) The cooling route is consistent with step (3) of Example 3.

[0034] That is, the high Bi substitution ferrite formula and green body preparation described in Comparative Example 2 are the same as those in Example 3. Since the high Bi substitution introduces more low-melting-point Bi2O3, Comparative Example 2 is set at 920°C (920°C is the conventional process sintering temperature of this formula) for continuous insulation for 15 h and the sintering route of the present invention adopted in Example 3 is sintered at 915°C (slightly lower than 920°C for comparison of the adjustability of temperature parameters) for a total insulation time of 15 h for comparison.

[0035] According to the microwave frequency application gyromagnetic material performance measurement method GB / T9633-2012, the ferromagnetic resonance line width ΔH, Curie temperature Tc, saturation magnetization 4πMs, relative dielectric constant ε of ferrite are measured. r The performance tests such as loss tangent tanδ are shown in Table 1. The ferrite grain micromorphology is analyzed using a scanning electron microscope (ZEISS SIGMA 300, Germany). The results are shown in the attached figure. Figure 7 shown.

[0036] Table 1 Main electromagnetic performance test results of various embodiments and comparative examples serial number <![CDATA[ε r ]]> tanδ ΔH (Oe) <![CDATA[4πM s (G)]]> <![CDATA[T c (℃)]]> Example 1 20 <![CDATA[<2×10 -4 ]]> 25 1900 250 Example 2 24 <![CDATA[<2×10 -4 ]]> 36 1950 225 Example 3 29 <![CDATA[<5×10 -4 ]]> 49 1800 185 Comparative Example 1 20 <![CDATA[<5×10 -4 ]]> 52 1880 246 Comparative Example 2 28 <![CDATA[<1×10 -3 ]]> 102 1760 177 From Table 1, we can see that Comparative Example 1 adopts the high dielectric constant garnet ferrite formula described in Example 1 and is sintered at 1050°C according to a conventional continuous heat preservation sintering process. The difference from Example 1 is that the sintering process is a continuous long-term heat preservation of 10 hours without alternating high and low temperatures. The results show that the ferromagnetic resonance line width ΔH (52 Oe) of the conventionally sintered high dielectric constant garnet ferrite is 27 Oe higher than that of the same ferrite (25Oe) prepared by the sintering process described in the present invention, and the tanδ is worse, and the dielectric constant changes less. Figure 5 With attached Figure 1 In comparison, the ferrite obtained by the conventional sintering process is over-burned, the grains grow abnormally, and a large number of pores appear; the ferrite obtained by the sintering process of the present invention has a grain size of more than 5μm, is relatively uniform and dense, and has a significant effect.

[0037] Comparative Example 2 adopts the high-medium garnet ferrite formula described in Example 3, and sintered at a low temperature of 920°C using a conventional continuous heat preservation sintering process. The difference from Example 3 is that its sintering process is a continuous long-term heat preservation of 15 h, without alternating high and low temperatures, and the high temperature section of Example 3 is kept at 915°C, which is lower than 920°C. The results show that compared with Example 3, the ferrite formula with a higher Bi substitution amount is prone to insufficient grain growth at a lower sintering temperature, smaller grain size, poor sintering quality, and a line width of up to 102 Oe. The ferrite obtained by the sintering method of the present invention in Example 3 has a better line width of 49 Oe; indicating that the ferrite with a high Bi substitution amount can also be optimized for line width by the sintering technology of the present invention at its corresponding lower sintering temperature, which improves grain growth to a certain extent, and ΔH is reduced by 53 Oe, with a significant effect.

[0038] The sintering technology route described in the above embodiment does not limit the number of high-temperature insulation sections and time for material sintering. The number of sintering sections and high-temperature insulation time are adjusted according to the specific Bi-substituted high dielectric material formula and product molding size design, and it is necessary to ensure that each high-temperature time is not too short to avoid insufficient sintering reaction and failure to achieve actual sintering effect.

[0039] The above embodiments and comparative examples further illustrate the technical solutions and beneficial effects of the present invention, but it cannot be determined that the specific implementation of the present invention is limited to these descriptions. Any modification, equivalent replacement, improvement, etc. made by ordinary technicians in the technical field of the present invention without departing from the present concept shall be deemed to belong to the protection scope of the present invention.

Claims

1. A sintering method for effectively reducing the ferromagnetic resonance line width of Bi-substituted high dielectric constant garnet ferrite, characterized in that: The sintering method comprises heating up - multiple stages of high temperature and low temperature alternation - cooling down.

2. The method according to claim 1, characterized in that: The composition of Bi-substituted high dielectric constant garnet ferrite is: 3-x-a Bi x Ca a M b Fe 5-b-δ O 12 , the M is selected from one of Sn, In, Zr, Ti, V, Al, and Ge, 0.8≤x≤1.6, 0.1≤b≤0.7, δ is the iron deficiency, 0.01≤δ≤0.1, and a is valence balanced according to the replacing element.

3. The method according to claim 1, characterized in that During sintering, a program-controlled bell furnace is used as the sintering furnace, and air or oxygen-containing atmosphere is used.

4. The method according to claim 1, characterized in that: The heating program is as follows: heating to 100°C in 50 to 100 minutes, heating to 200°C in 120 to 200 minutes, heating to 400°C in 150 to 400 minutes, heating to about 100°C to 200°C below the sintering temperature at a heating rate of ≤2.5°C / min, and finally heating to the maximum sintering temperature or a temperature within 15°C below the maximum sintering temperature in 150 to 300 minutes.

5. The method according to claim 1, characterized in that The multi-stage high-temperature and low-temperature alternating route undergoes at least two high-temperature insulation processes.

6. The method according to claim 5, characterized in that The multi-stage high-temperature and low-temperature alternating route is: high-temperature insulation section-cooling section-low-temperature insulation section-heating section-high-temperature insulation section.

7. The method according to claim 5, characterized in that The insulation time of each high-temperature insulation section is not less than 5 hours, and the insulation temperature is within 15°C lower than the maximum temperature. The insulation time of each low-temperature insulation section is not less than 2 hours. The temperature of the cooling section is reduced to 200-300°C below the temperature of the sintering high-temperature section. The cooling rate to the cooling section is 1°C / min-2.5°C / min, and the heating rate from the low-temperature insulation section to the high-temperature insulation section is ≤2.5°C / min.

8. The method according to claim 1, characterized in that: The cooling route is natural cooling or cooling at a rate of 1°C / min to 2.5°C / min.

Citation Information

Patent Citations

  • Submicron alumina ceramic material and preparation method thereof

    CN101704680A

  • High-low temperature circular sintering method for electronic ceramic materials

    CN101844927A

  • Preparation method of rare-earth-free garnet ferrite with high dielectric and high Curie temperature

    CN118145977A